Methodical Approaches to Estimate Hotel Facilities’ Efficiency - NIKOLSKAYA, Elena Yurievna; ANZOROVA, Svetlana Petrovna; POTAPOV, Sergey Victoroviсh; DEKHTYAR, Galina Maxovna; LEBEDEV, Kostyantyn Anatol'evich (Journal of Environmental Management and Tourism; Vol 9 No 8 (2018): JEMT Volume IX Issue 8(32) Winter 2018, 2019)
The article deals with the development of approaches aimed at increasing the competitiveness of hotel business operators in present-day conditions. It is revealed that there is no uniform approach to a comprehensive assessment of hotel facilities operating efficiency. The proposed scheme of grouping of indicators for assessing the operation effectiveness of the hotel business according to criterial directions makes it possible to define functional and estimated indicators. The dynamics analysis of hotel facilities’ operating efficiency is carried out based on clusters within groups of functional and estimated indicators as well as within criterial directions, which allowed uncovering the content of the problems arising before executives during search for ways to enhance operating efficiency of the hotel facilities. The article offers a clear organization of the analytical process to identify the features of the hotel enterprises’ status and development in the context of individual groups, as well as to carry out qualitative and effective economic analysis.